Tandem laser-gas metal arc welding joining of 20 mm thick super duplex stainless steel: An experimental and numerical study. (May 2020) - Mathieu, A; Tkachenko, I; Jouvard, JM; Tomashchuk, I
The present work covers the topic of strains and stresses prediction in case of welded steel structures. Steel sheets of 20 mm thickness made in UR™2507Cu are welded using a laser and gas metal arc welding processes combination. The focused laser beam leads the arc in a Y-shape chamfer geometry. Both sources are 20 mm apart from each other in order to avoid any synergic effect with each other. In order to predict residual strain, a 3D unsteady numerical simulation has been developed in COMSOL finite element software. A volume heat source has been identified based on the temperature measurements made by 10 K-type thermocouples, implanted inside the workpiece. The 50 mm deep holes are drilled in the workpiece using dye-sinking Electrical Discharge Machining (EDM) machine. Before the implantation in the hole, each thermocouple is surrounded by Inconel sheathing. Hot junctions of the thermocouples are positioned in a way to feel two advancing molten pools. The equivalent heat source is composed of three sources. First one is a Goldak source that represents the molten pool induced by gas metal arc welding. The second one is a cylinder with an elliptic cross-section that represents the focused laser beam penetrating into the workpiece. The third one is a surface Gaussian source that represents energy radiated by arc and blocked by workpiece surface. Concerning mechanical simulation, an elasto-plastic behavior with isotropic hardening is implemented. A weak coupling is established between equations governing heat transfer and mechanics thanks to the temperature dependent coefficient of linear expansion. This numerical simulation made with some simplifying assumptions predicts an angular distortion and a longitudinal shrinkage of the welded structure. The numerical results are consistent with the displacements measured by digital image correlation method.